Effect of daily sildenafil on patients with absent nocturnal erections due to pelvic fracture urethral disruption: a single‐centre experience. (9th February 2016) - Peng, J.; Zhang, Z.; Gao, B.; Yuan, Y.; Cui, W.; Tang, Y.; Song, W.; Xin, Z.
Summary: Erectile dysfunction (ED) is a common sequel of pelvic fracture urethral disruption. Those patients with nocturnal erections may respond favourably to sildenafil; however, little is known about the response to sildenafil in patients with absent nocturnal erections. The aim was to evaluate the response to the treatment of sildenafil 50 mg taken once daily in the patients with absent nocturnal erections. From January 2008 to December 2011, a total of 28 patients with absent nocturnal erections were evaluated. We recorded nocturnal penile tumescence and rigidity with an erectometer. If nocturnal erections were absent for three nights, patients were administrated sildenafil 100 mg at bedtime and tested again at the fourth night. Penile duplex ultrasound with intracavernous injection was performed to define the cause of ED. All patients received a daily dose of sildenafil 50 mg for 12 weeks. Response to sildenafil treatment was defined as sustained erections allowing vaginal penetration and intercourse. Twenty‐three (78%) patients completed the daily sildenafil treatment, and follow‐up was available. The nocturnal erections at the fourth night in 13 patients (46.4%) were improved. About 61.5% (8/13) reported effective response to daily sildenafil. The improvement of nocturnal erections induced by sildenafil taken at bedtime might predict the response to sildenafil taken daily.